Cooperation and Competition When Bidding for Complex Projects: Centralized and Decentralized Perspectives - Skowron, Piotr (2017)
To successfully complete a complex project, agents (companies or individuals) must form a team with the required competencies and resources. A team can be formed either by the project issuer based on individual agents' offers (centralized formation) or by the agents themselves (decentralized formation) bidding for a project as a consortium. The authors investigate rational strategies for agents, propose concepts to characterize the stability of winning teams and study computational complexity of finding these concepts of stability.